Short-term Memory Optimization through Physical Work Environment Determination - Putra, Perdana Suteja; Nabila, Meidina; Rizka Putri, Aurelia (Program Studi Magister Ergonomi Fisiologi Kerja Pascasarjana Universitas Udayana Denpasar Bekerjasama dengan Perhimpunan Ergonomi Indonesia (PEI), 2023)
One element that affects a worker's performance is their work environment such as noise, lighting, and temperature, particularly when it comes to memorizing tasks that require short-term memory. Therefore, it is needed to design the optimum work environment to optimize the work of short-term memory that may lead the increase of employee’s performance. The approach using Taguchi experimental design using L4 for each interior and outer array. Then, three control variables with two degrees of each are utilized to produce the optimum possible combination of working environment settings for short-term memory optimization. Two responses were measured to determine the effect of control and noise variables on short-term memory performance which are the correct answer and processing time on the testing using Design-tools application. According to the findings, the effects of noise, lighting, and temperature on short-term memory performance were 63.02%, 0.99%, and 26.63%, respectively for number of correct answer response. In addition, short-term memory has noise, lighting, and temperature of 51.9%, 14.54%, and 1.81%, respectively, for process time response. Furthermore, the VIKOR technique is utilized to achieve optimal work ambient conditions such as low noise of approximately 42dB, high illumination of 300-700 lux, and low temperature of 210-250 Celsius, which may contribute to optimal short-term memory function.